Mycelial growth observation of Pleurotus eryngii (Higher Basidiomycota) In Vitro - Owaid, Mustafa Nadhim; Al-Saeedi, Sajid SS; Abed, Idham Ali (International Journal of Environment, 2016)
Five agro-substrates including date palm fibers (fibrillum), wheat straw, white sawdust and their combinations were investigated to grow Pleurotus eryngii. The longer mycelium complete time within bags was 20 days on sawdust (S4), in contrast, the shorter time for mycelium overgrew was completed after 15 days on date palm fiber (S5). In significant (p